2005
DOI: 10.1254/jphs.fmj04005x4
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Pathophysiology of Proteinase-Activated Receptors (PARs): PARs in the Respiratory System: Cellular Signaling and Physiological/Pathological Roles

Abstract: Abstract. Proteinase-activated receptors (PARs), a family of G protein-coupled receptors, are widely distributed in the mammalian body, playing a variety of physiological / pathophysiological roles. In the respiratory systems, PARs, particularly PAR-2 and PAR-1, are expressed in the epithelial and smooth muscle cells. In addition to the G q/ 11 -mediated activation of the phospholipase Cb pathway, epithelial PAR activation causes prompt and / or delayed prostanoid formation, leading to airway smooth muscle rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…We previously showed that Pen c 13 activates PAR-1 and PAR-2 through activation of phospholipase C␤ via G q/11 ␣ protein, a common pathway for G protein-coupled receptors, and produces inositol triphosphate, followed by Ca 2ϩ mobilization (34). We therefore investigated whether Pen c 13 induced IL-8 release via phospholipase C activation and found that this was the case.…”
Section: Discussionmentioning
confidence: 94%
“…We previously showed that Pen c 13 activates PAR-1 and PAR-2 through activation of phospholipase C␤ via G q/11 ␣ protein, a common pathway for G protein-coupled receptors, and produces inositol triphosphate, followed by Ca 2ϩ mobilization (34). We therefore investigated whether Pen c 13 induced IL-8 release via phospholipase C activation and found that this was the case.…”
Section: Discussionmentioning
confidence: 94%
“…Many common environmental irritants and aeroallergens, such as extracts from house dust mites, cockroaches, and numerous fungal species, have been reported to exhibit protease activity (2,23,30,31), which is implicated in bronchial inflammation, likely due in part to the release of inflammatory cytokines from BECs (5,8). Although proteases can exert their effects on cell function in several ways, specific G protein-coupled receptors, termed protease-activated receptors (PARs), have been identified, and these have been shown to mediate many of the physiological responses of cells to proteases (14,31). Accordingly, we tested whether proteases in HDE contribute to the dust-induced inflammatory response in BECs, in lung tissue slices, and in a murine model of airway disease, and whether this response is mediated through PARs.…”
mentioning
confidence: 99%
“…PAR 2 is extensively but unevenly distributed in the mammalian body, including the nervous, circulatory, gastrointestinal, and respiratory systems, modulating a variety of functions under physiological and/or pathological conditions (Cocks et al, 1999;Cicala et al, 2001a;Kawabata et al, 2001aKawabata et al, ,b, 2004Vergnolle et al, 2001;Ossovskaya and Bunnett, 2004;Sekiguchi and Kawabata, 2004a,b;Kawabata and Kawao, 2005). PAR 2 , like other PARs, couples to G q/11 protein that mediates activation of phospholipase C ␤ followed by formation of inositol triphosphate and diacylglycerol and also seems to trigger activation of other multiple signaling pathways, including the mitogen-activated protein kinase (MAPK) cascades in distinct cell types (Ossovskaya and Bunnett, 2004;Sekiguchi and Kawabata, 2004).…”
mentioning
confidence: 99%
“…In the respiratory system, PAR 2 plays a dual role, being both anti-inflammatory/protective and proinflammatory (Cocks et al, 1999;Cicala et al, 2001b;Moffatt et al, 2002;Schmidlin et al, 2002;Kawabata and Kawao, 2005). PAR 2 is expressed in airway epithelial cells, and stimulation of PAR 2 with PAR 2 -activating peptides or trypsin causes epithelial prostaglandin E 2 (PGE 2 )-dependent relaxation in the isolated tracheal and bronchial tissues from humans, guinea pigs, rats, and mice (Cocks et al, 1999;Lan et al, 2001).…”
mentioning
confidence: 99%